Molecular Design of Highly Efficient Heavy‐Atom‐Free Triplet BODIPY Derivatives for Photodynamic Therapy and Bioimaging. Issue 23 (24th March 2020) - Nguyen, Van‐Nghia; Yim, Yubin; Kim, Sangin; Ryu, Bokyeong; Swamy, K. M. K.; Kim, Gyoungmi; Kwon, Nahyun; Kim, C‐Yoon; Park, Sungnam; Yoon, Juyoung
Abstract: Novel BODIPY photosensitizers were developed for imaging‐guided photodynamic therapy. The introduction of a strong electron donor to the BODIPY core through a phenyl linker combined with the twisted arrangement between the donor and the BODIPY acceptor is essential for reducing the energy gap between the lowest singlet excited state and the lowest triplet state (Δ E ST ), leading to a significant enhancement in the intersystem crossing (ISC) of the BODIPYs. Remarkably, the BDP‐5 with the smallest Δ E ST (ca. 0.44 eV) exhibited excellent singlet oxygen generation capabilities in both organic and aqueous solutions. BDP‐5 also displayed bright emission in the far‐red/near‐infrared region in the condensed states. More importantly, both in vitro and in vivo studies demonstrated that BDP‐5 NPs displayed a high potential for photodynamic cancer therapy and bioimaging. Abstract : Twisted sensitizers : Twisted D‐BODIPY π‐conjugated systems with a phenyl linker as novel heavy‐atom‐free triplet BODIPY photosensitizers were prepared for imaging‐guided photodynamic therapy. BDP‐5 NPs were successfully applied in vitro and in vivo and exhibited a high potential for photodynamic cancer therapy and bioimaging.